The effect of tofu cake as an additional feed on local male sheep’s water consumption and their physiological response - Wayan Sukarya Dilaga; R. Adiwinarti (International Journal of Science and Engineering, 2011)
Feeds are very important for the growth of animals due to it is contained almost all nutrients needed by the animals. Feeds are not only influence the animal growth but also their physiological response. The objective of this research was to investigate the effect of tofu cake as an additional feed replacing commercial concentrate on local male sheep’s water consumption and their physiological response such as body temperature, pulse, and rate of exhalation. The selected 15 local male sheep (in the age of 8-9 month with initial weight 12.53 ± 1.19 kg) were housed individually in cage for about 14 weeks include 4 weeks adaptation period and 10 weeks experiment.The experiment was conducted using completely randomized design with 3 different treatments and 5 times repetition; T0 = ad libitum grass field + commercial concentrate, T1= ad libitum grass field + wet tofu cake, T2= ad libitum grass field + dried tofu cake, and water were provided in ad libitum method. Data analysis was done using analysis of variance (ANOVA) followed by Duncan’s multiple range test. The result shown that dried tofu cake as an additional feed replacing commercial concentrate was able to increasing the water consumption of local male sheep. Meanwhile the physiological test performed stable in the present of wet or dried tofu cake. Keywords— alternative feed, physiological response of male sheep